Free indirect speech in Croatian oral folk tales - Laco, Gordana; Ninčević, Siniša (Stylistyka, 2021)
This paper considers free indirect speech (FIS) in Croatian oral folk tales (fairy tales, legends, oral tradition and fables). Oral folk tales (folklore) from all parts of Croatia, and that in all three Croatian dialects (the Shtokavian, the Chakavian, and the Kajkavian) have been analysed. Special attention is paid to first-hand accounts according to authentic tellings in recent times. The types of FIS that are commonly attributed to the linguo-stylistic characteristics of modern art prose have been con[1]sidered. Additionally, some techniques that also indicate SNG have been analysed, which has neither been noticed nor described in the hitherto Croatian philological literature. It is concluded that FIS is a linguo-stylistic device which affects the way of delivering (creating) a story, but it is also a feature which distinguishes one tale from another.